2018
DOI: 10.1038/s41434-018-0049-0
|View full text |Cite
|
Sign up to set email alerts
|

GDNF-mediated rescue of the nigrostriatal system depends on the degree of degeneration

Abstract: Glial cell-line derived neurotrophic factor (GDNF) is a promising therapeutic molecule to treat Parkinson’s disease. Despite an excellent profile in experimental settings, clinical trials testing GDNF have failed. One of the theories to explain these negative outcomes is that the clinical trials were done in late-stage patients that have advanced nigrostriatal degeneration and may therefore not respond to a neurotrophic factor therapy. Based on this idea, we tested if the stage of nigrostriatal degeneration is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Brain study in PD patients found that SNpc cells and putamen dopaminergic terminals appear to be lost during the first 4–7 years of diagnosis. This indicates that the rescue of the nigrostriatal system mediated by GDNF relies on the degree of degeneration (Quintino et al, 2019 ). To rescue the nigrostriatal system and motor deficits, GDNF had to be present in the striatum such that a significant amount of damaged SNpc neurons remain to respond to therapy.…”
Section: Why Has Gdnf Failed In Clinical Trials?mentioning
confidence: 99%
“…Brain study in PD patients found that SNpc cells and putamen dopaminergic terminals appear to be lost during the first 4–7 years of diagnosis. This indicates that the rescue of the nigrostriatal system mediated by GDNF relies on the degree of degeneration (Quintino et al, 2019 ). To rescue the nigrostriatal system and motor deficits, GDNF had to be present in the striatum such that a significant amount of damaged SNpc neurons remain to respond to therapy.…”
Section: Why Has Gdnf Failed In Clinical Trials?mentioning
confidence: 99%
“…Identification of the temporal characteristics of endogenous gdnf activation and de-activation during regeneration would offer a paradigm shift for therapeutic regulation of GDNF expression. Correct spatiotemporal application of GDNF is crucial to successfully halt or rescue neuronal deterioration resulting from neurodegenerative diseases such as PD (Eggers et al, 2019;Quintino et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…HO-1-derived astrocytic GDNF secretion reduces neuronal cell death [150]. Lentiviral vectors expressing GDNF are delivered to the striatum of rats following Parkinson's disease-like injury [151]. In the group of animals where GDNF expression is switched on during degeneration, neurons are rescued and there is a reversal of motor deficits; in contrast, in the group of animals where GDNF expression is switched on 21 d after the injury, neurons are not rescued [151].…”
Section: Glial Cell-line Derived Neurotrophic Factor (Gdnf)mentioning
confidence: 99%